Comparing knowledge, attitudes, and practices in cardiovascular disease prevention and health promotion between community and hospital pharmacists in Saudi Arabia: A cross-sectional study - Easwaran Vigneshwaran; Sultan M. AlShahrani; Abdullah R. Alanzi; Asif Ansari Shaik Mohammad; Mantargi Mohammed Jaffar Sadiq; Noohu Abdulla Khan; Sirajudeen Shaik Alavudeen (Elsevier, 2024)
Purpose: Saudi Arabia is one of the leading nations in the world in terms of the high frequency of chronic diseases and their associated risk factors. Knowledge and awareness are crucial for pharmacists to play an active role in the prevention of cardiovascular diseases (CVD). The current study assessed the pharmacists' knowledge, attitude, and practice to determine the potential differences with respect to their respective practice settings toward CVD prevention and related health promotions. Methods: It is a cross-sectional study targeted the registered pharmacists in the Kingdom of Saudi Arabia. An online questionnaire was prepared, and the link was circulated through various social media platforms. Descriptive statistics, multivariate linear regression analysis and chi square test were used to analyze the data accordingly. Results: A total of 324 pharmacists were included in the study. Among these, 157 (48.4 %) were community pharmacists, and the remaining were hospital pharmacists (51.6 %). No significant differences in knowledge scores were observed between community and hospital pharmacists. The mean attitude score among community and hospital pharmacists was found to be 26.40 ± 5.125 and 25.09 ± 5.393 respectively, which was statistically significant (p = 0.026). Similarly, the total practice scores across the settings were statistically significant (p = 0.02). Gender plays a significant role in terms of knowledge scores among both community and hospital pharmacists (p = 0.016 & 0.029). Gender, professional practice experience, and number of prescriptions handled and prescriptions with CVD medications showed significant differences in the distribution of positive attitudes and good practice frequency between community and hospital pharmacists. Conclusion: It is evident that there is a deficiency in knowledge among hospital pharmacists compared to community pharmacists. Which indicates that there is a need for a rigorous continuous pharmacy education covering the fundamental aspects of CVD primary prevention and health promotion among pharmacists, given more focus on hospital pharmacists.